Determining Orthorexia Nervosa Tendency among the Students of Health Sciences Faculty: The Case of Artvin Coruh University - , Eda Dokumacioglu, Kudret Badem, Uçar Kucuk (Archives of Current Research International, 2019)
Eating disorders is a general term used for grouping all the problems related to eating attitudes under one title and for expressing these problems. Orthorexia nervosa (ON), also known as “obsession of healthy eating” recently happened to be the research topic of clinicians worldwide. This study was conducted to evaluate the association between eating attitudes and orthorexia nervosa in university students. The research population was comprised of 379 university students in the departments of nutrition and dietetics and nursing. The data was collected by the survey form questioning some of the socio-demographic and anthropometric properties of the students; and as for the data collection tool, ON tendency was determined by ORTHO-11 test and the information regarding anorexia and buliminia nervosa was gathered by “Eating Manner Test (EAT-40). Mean age of the students was found as 20.09±1.47 years, mean body weight as 60.55±10.01 kg, and mean height as 168.08±7.91 cm. Mean BMI of the all participating students is found as 21.6±2.12 as normal weight (18.5-24.9). EAT-40 points of the female were found to be significantly higher in comparison to that of the male (p<0.05). ORTHO-11 points of the male students were found to be significantly higher as compared to that of female students (p<0.05). Eating disorders will tend to increase as long as the concepts of beauty, good look and appeal are based on low body mass index. We also believe that the youg population who are most influenced by such popular trends need to acquire truly healthy nutrition habits through training and increase their quality of life.